Characteristics of Mangium (Acacia mangium) Bark Extract with Some Extraction Time and Its Application to Cotton Fabric Dyeing - Diana Sylvi; Ismed Ismed; Sonia Merlin (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2022)
This study aims to determine the effect of extraction time on the characteristics of mangium bark extract and its application to cotton textile coloring. This study used a completely randomized design (CRD) with 5 treatments and 3 replications, A (10 minutes extraction), B (20 minutes extraction), C (30 minutes extraction), D (40 minutes extraction) and E (50 minutes extraction). . The results showed that the difference in extraction time had a significant effect on the yield, moisture content, tannin content and color of the mangium bark extract. Extraction time of mangium bark for 40 minutes is the optimum extraction time based on analysis of yield, tannin content and color of the extract. Yield analysis at extraction time of 40 minutes obtained the highest yield of 10.72% and tannin content of 15.67%. The cotton cloth that had been dyed with mangium bark extract changed color from yellow to red. The results of the color change test on cotton cloth that had been dyed with mangium bark extract showed that the results did not show very small to small changes when soaked in hot water and detergent.